2021
DOI: 10.3389/fmed.2020.569759
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use and the Incidence of Hepatocellular Carcinoma in Patients With Hepatitis B Virus or Hepatitis C Virus Infection: A Meta-Analysis of Cohort Studies

Abstract: Background: The association between aspirin use and the incidence of hepatocellular carcinoma (HCC) in patients with hepatitis B virus (HBV) or hepatitis C (HCV) virus infection remains not fully determined. A meta-analysis was performed to summarize the findings of cohort studies.Methods: Relevant cohort studies were retrieved via a search of PubMed Cochrane's Library and Embase databases. A random-effect model was used to pool the results. Subgroup analyses were performed to evaluate the influence of study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…36 Recent metaanalyses of population-based cohorts or at-risk patients with chronic liver disease revealed that aspirin was associated with a significantly decreased risk of HCC development (HR, 0.51-0.59; RR, 0.73). [37][38][39] However, aspirin use was reported to slightly increase the risk (RR, 1.15-1.32) of gastrointestinal bleeding as a major adverse event; 37,38 therefore, the potential benefits from aspirin must be weighed against the potential for bleeding in patients with chronic liver disease. Particularly, the benefits from aspirin use regarding lowering HCC risk were reportedly lacking (aHR, 1.00; 95% CI, 0.85-1.18) in patients with HBV-related cirrhosis in a recent analysis of Korean population-based administrative database.…”
Section: Primary Prevention Of Hccmentioning
confidence: 99%
“…36 Recent metaanalyses of population-based cohorts or at-risk patients with chronic liver disease revealed that aspirin was associated with a significantly decreased risk of HCC development (HR, 0.51-0.59; RR, 0.73). [37][38][39] However, aspirin use was reported to slightly increase the risk (RR, 1.15-1.32) of gastrointestinal bleeding as a major adverse event; 37,38 therefore, the potential benefits from aspirin must be weighed against the potential for bleeding in patients with chronic liver disease. Particularly, the benefits from aspirin use regarding lowering HCC risk were reportedly lacking (aHR, 1.00; 95% CI, 0.85-1.18) in patients with HBV-related cirrhosis in a recent analysis of Korean population-based administrative database.…”
Section: Primary Prevention Of Hccmentioning
confidence: 99%
“…Moreover, Xiaofei Li and colleagues performed a meta-analysis of seven cohort studies involving 120,945 adult patients with hepatitis B virus (HBV) or HCV infection. Pooled results showed that ASA use was independently associated with a reduced risk of HCC [ 151 ]. Some preclinical evidence also supports ASA’s role in liver disease prevention and progression for hepatocellular carcinoma and hepatitis.…”
Section: Resultsmentioning
confidence: 99%
“…6 In contrast, a subgroup analysis using Korean and Taiwanese National Health Insurance database found no association between aspirin and HCC in cirrhotic patients 66,69,70 . Lastly, a recent meta-analysis of individuals with viral hepatitis demonstrated that aspirin use was associated with a lower risk of HCC but the risk reduction rate was smaller than in non-cirrhotic patients (HR = 0.85, 95% CI: 0.76-0.95, HR = 0.64, 95% CI: 0.50, 0.83) 78 .…”
Section: %) 68mentioning
confidence: 99%